The 4 lenses of innovation a power tool for creative thinking - Gibson, Rowan (Wiley, 2015)
"By asking how the world's top innovators - Steve Jobs, Richard Branson, Jeff Bezos and many others - came up with their game-changing ideas, ... Rowan Gibson identifies four key business perspectives that will enable you to discover groundbreaking opportunities for innovation and growth: Challenging orthodoxies: what if the dominant conventions in your field, market, or industry are outdated, unnecessary or just plain wrong? Harnessing trends: where are the shifts and discontinuities that will, now and in the future, provide the energy you need for a major leap forward? Leveraging resources: how can you arrange existing skills and assets into new combinations that add up to more than the sum of their parts? Understanding needs: what are the unmet needs and frustrations that everyone else is simply ignoring?"--Publisher's description.